Food safety regulation and its implication on Chinese vegetable exports. (November 2015) - Dou, Lei; Yanagishima, Koji; Li, Xin; Li, Ping; Nakagawa, Mitsuhiro
Highlights: We estimated the effects of MRLs by level and number changes on vegetable exports. Export inhibiting effect of expanding MRLs number in importing markets was reported. Export promoting effect of stringent regulation in exporting country was verified. Abstract: Growing concerns with the application of highly toxic pesticides and the growing world demands for food direct our attentions to the food safety as well as to the global arrangement of food production. In China, expansion of its vegetable exports brought the attention of policy planners to the international food safety regulations. This paper reported the findings from the investigation about a relationship between trades of food and food safety, by focusing on the relationship between Chinese vegetable exports and the maximum residue limits of pesticides (MRLs) regulation set by the importing countries and exporting country. The revealed trade's behavior showed that impacts of MRLs should be seen through two types of information, one was the extent of coverage of regulation measured by the number of pesticides placed under the control, and the other was the regulated residue levels. Probably because the achieved vegetable production growth was supported by the extensive use of many kinds of pesticides, the expanding of the number of regulated pesticides in importing markets, was more likely to act as a barrier to China's vegetable exports compared to the effect of stringency increase of MRLs level. Importing countries' GDP reflecting the market potential showed significantly positive effects on Chinese vegetable exports, while the effects of vegetable production and tariff rate on exports were weakened after years of improvement of productivity and worldwide policy environment. Our results verified the export promoting effect of stringent regulations in exporting country on its trade. These findings strongly suggested that Chinese authorities need to move fast to catch-up to the growing concerns of international importers both from relevant policy planning and implementing, to capture economic growth in the medium-long term.